Cytomorphological overview of fine-needle aspiration breast utilizing the International Academy of Cytology – Yokohama system of reporting - Manjusha Punjaji Tambse,; Dhiraj Bapu Nikumbh,; Samruddhi Sudhir Thakare,; Shalaka Deepak Tupkari, (Asian Journal of Medical Sciences, 2023)
Background: Benign and malignant lesions of breast are one of the most common causes of palpable masses seen in women. Fine-needle aspiration cytology (FNAC) is the important modality of diagnosis of breast lumps. Previously, there were no uniform criteria for reporting breast FNAC. To overcome this problem, the newly designed system – International Academy of Cytology (IAC) – Yokohama system of reporting was implemented in 2016. The system offers a structured report to the patient. Aims and Objectives: This study aims to categorize breast FNAC according to the IAC – Yokohama system of reporting, to calculate the sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and diagnostic accuracy of the test, and to analyze the cytomorphological spectrum of various breast lesions. Materials and Methods: A total of 210 patients presenting with breast lump in cytology section were subjected to FNAC using a 22 gauge needle under all aseptic precautions. Detailed clinical history was taken. All cytology and histopathology examination slides (wherever available) were thoroughly studied. FNAC smears were reported using IAC – Yokohama system of reporting. Results: In our study, benign category (C2) was most commonly seen in 73.33% of cases, followed by 10.48% of cases of atypical probably benign (C3), 2.38% of cases were reported as suspicious (C4), and 11.43% of cases were reported as malignant (C5). Cytohistopathological concordance was seen in 38 cases (88.4%) whereas five cases were reported as discordant. Sensitivity and specificity of the test for the diagnosis of malignancy were 81% and 100%, respectively. PPV was 100%. NPV was 90.90%. Diagnostic accuracy of the test was 93.47%. Conclusion: The newer IAC – Yokohama system of reporting of breast FNAC is simple, has clear diagnostic criteria hence boost up the confidence as well has uniformity of reporting by cytopathologist, and increases the understanding and uniformity in assessment by the attending clinician which help in improving the communication between the pathologist and the treating clinician.